2010
DOI: 10.1214/ejp.v15-807
|View full text |Cite
|
Sign up to set email alerts
|

The Symbol Associated with the Solution of a Stochastic Differential Equation

Abstract: Let (Z t ) t 0 be an R n -valued Lévy process. We consider stochastic differential equations of the formwhere Φ : R d → R d×n is Lipschitz continuous. We show that the infinitesimal generator of the solution process (X x t ) t 0 is a pseudo-differential operator whose symbol p :For a large class of Feller processes many properties of the sample paths can be derived by analysing the symbol. It turns out that the process (X x t ) t 0 is a Feller process if Φ is bounded and that the symbol is of the form p(x, ξ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 27 publications
1
76
0
Order By: Relevance
“…We refer to [29,30] where many examples of this kind are studied. Moreover, we refer to [27] and, in particular, to [39,40] where q(x, ξ) was calculated as q(x, ξ) = − lim t→0 E x e iξ(Xt−x) − 1 t .…”
Section: Towards a Geometric Understanding Of Transition Functions Ofmentioning
confidence: 99%
“…We refer to [29,30] where many examples of this kind are studied. Moreover, we refer to [27] and, in particular, to [39,40] where q(x, ξ) was calculated as q(x, ξ) = − lim t→0 E x e iξ(Xt−x) − 1 t .…”
Section: Towards a Geometric Understanding Of Transition Functions Ofmentioning
confidence: 99%
“…Note that λ t (q, p) = e −tH(q,p) in general. 3 Some possibilities of constructing and approximating the symbol of the semigroup starting from the symbol of the generator can be found in [6,13,37]. Many sufficient conditions for a function −H(q, p) to be the 1-symbol of a Feller generator are known.…”
Section: Hamiltonian Feynman Formula For Feller Semigroupsmentioning
confidence: 99%
“…[16], chapter 8) it is sometimes hard to transform it into the Skorokhod-type. The symbol on the other hand can occasionally be written down directly and in a neat way: In [21], it is shown that the symbol of the solution of the Lévy driven SDE X t = X 0 + t 0 f X s− dZ s is f x where is the characteristic exponent of the driving Lévy process Z s . (iv) While the coefficients depend on the choice of the SDE-type and the truncation function (in (2) we have chosen 1 u ≤1 ; someone interested in limit theorems would probably choose a continuous function), this is not the case for the symbol.…”
Section: Böttcher and Schnurrmentioning
confidence: 99%
“…In [22], theorem 5.7 (see also [21]), it is shown that, given (6), the Itô process X t t≥0 has the symbol p d × d → given by…”
Section: Proof Of the Theoremmentioning
confidence: 99%